Financial Risk Literacy as Predictor of Preventive Behavior Toward Illegal Online Lending Among Students - Kuntadi, Yahya Agung; Akyuwen, Roberto (Jurnal Riset Ekonomi dan Bisnis, 2026)
This study examines the role of Financial Risk Literacy (FRL) in shaping preventive behavior toward illegal online lending among university students. Unlike prior fintech research that primarily focuses on technology adoption, this study shifts attention to financial protection behavior. A cross-sectional survey was conducted involving 106 undergraduate students. FRL was measured using nine risk-oriented items, while preventive behavior was assessed using three action-based indicators. Intention to avoid illegal online lending was measured using a single item and treated as an observed mediator variable. Mediation analysis was performed using bootstrapping procedures. The results indicate that FRL significantly predicts intention to avoid illegal online lending and directly influences preventive behavior. Bootstrapping analysis confirms a significant indirect effect, indicating partial mediation. These findings suggest that FRL operates through both cognitive intention formation and direct behavioral activation pathways. This study contributes to the financial behavior literature by emphasizing risk-focused literacy as a protective cognitive asset in digital financial environments.